A survey of interprofessional activity of acute and long‐term care employed nurse practitioners. Issue 9 (20th February 2015) - Hurlock‐Chorostecki, Christina; van Soeren, Mary; MacMillan, Kathleen; Sidani, Souraya; Collins, Laura; Harbman, Patti; Donald, Faith; Reeves, Scott
Abstract Purpose To describe activities of interprofessional (IP) care, a key aspect of high‐quality care, performed by nurse practitioners (NPs) employed in acute and long‐term care institutions. Data sources We developed and tested a new theory‐driven process tool to quantify NP everyday activities of IP care. We then invited NPs in acute and long‐term care to complete the IP self‐assessment tool (IPSAT). Conclusions The IPSAT is a validated tool shown to be reliable for use with NPs. Testing with other healthcare professionals is suggested. More than 50% of NPs engage in all activities of IP care. Many engage in shared decision making, professional relationship, communication, and partnership or collaboration activities on most work days. Less‐common activities were interdependence and collective problem solving including efforts to create role clarity. Implications for practice It is important to evaluate the everyday use of activities that enhance high‐quality care. Awareness and enhanced knowledge of IP care activities such as promoting interdependence, collective problem solving, and ensuring role clarity will improve care quality. The tool results are valuable for practicing NPs and their educators to reflect on practice and advance knowledge to influence purposeful engagement in interprofessional care.